The implementation of integral concepts in physics problem-solving by students with a conceptual blending framework approach - Fitriah, Fitriah; Sugiatno, Sugiatno; Noviani, Evi (Indonesian Journal of Science and Mathematics Education, 2024)
This research employed a qualitative descriptive approach to explore the application of integral concepts in solving physics problems with the conceptual blending framework. The sample of 26 students were categorized into four groups. The research investigated how different groups applied conceptual blending in addressing physics problems involving integrals. The findings revealed diverse understandings and approaches across the groups, with Group 4 exhibiting a more integrated understanding of physics and mathematics concepts. The study highlighted the effectiveness of conceptual blending in fostering a deeper comprehension of complex concepts in physics and mathematics, suggesting a potential pedagogical strategy to enhance students' problem-solving skills and theoretical understanding. This research contributes to the field by demonstrating the nuanced ways students engage with interdisciplinary concepts, offering insights for educators to refine teaching methodologies in integrating mathematics into physics education.